Toll-like Interleukin 1 Receptor Regulator Is an Important Modulator of Inflammation Responsive Genes - Kashem, Mohammad Abul; Li, Hongzhao; Toledo, Nikki Pauline; Omange, Robert Were; Liang, Binhua; Liu, Lewis Ruxi; Li, Lin; Yang, Xuefen; Yuan, Xin-Yong; Kindrachuk, Jason; Plummer, Francis A.; Luo, Ma (Frontiers in Immunology, 2019)
TILRR (Toll-like interleukin-1 receptor regulator), a transcript variant of FREM1, is a novel regulatory component, which stimulates innate immune responses through binding to IL-1R1 (Interleukin-1 receptor, type 1) and TLR (Toll-like receptor) complex. However, it is not known whether TILRR expression influences other genes in the NFκB signal transduction and pro-inflammatory responses. Our previous study identified FREM1 as a novel candidate gene in HIV-1 resistance/susceptibility in the Pumwani Sex worker cohort. In this study, we investigated the effect of TILRR overexpression on expression of genes in the NFκB signaling pathway in vitro. The effect of TILRR on mRNA expression of 84 genes related to NFκB signal transduction pathway was investigated by qRT-PCR. Overexpression of TILRR on pro-inflammatory cytokine/chemokine(s) secretion in cell culture supernatants was analyzed using Bioplex multiplex bead assay. We found that TILRR overexpression significantly influenced expression of many genes in HeLa and VK2/E6E7 cells. Several cytokine/chemokine(s), including IL-6, IL-8 (CXCL8), IP-10, MCP-1, MIP-1β, and RANTES (CCL5) were significantly increased in the cell culture supernatants following TILRR overexpression. Although how TILRR influences the expression of these genes needs to be further studied, we are the first to show the influence of TILRR on many genes in the NFκB inflammatory pathways. The NFκB inflammatory response pathways are extremely important in microbial infection and pathogenesis, including HIV-1 transmission. Further study of the role of TILRR may identify the novel intervention targets and strategies against HIV infection.